Intervention Without Intervening? - Cooper, A. author. aut Link
VIII, 184 p.
Keywords: This book looks at the evolution of the Organization of American States (OAS) multilateralism for democracy and the lessons its experience holds for other multilateral contexts. It also tackles the theoretical challenge of bridging the traditional divide between international relations and comparative politics.